2018
DOI: 10.18632/oncotarget.23873
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of acute myeloid leukemia patients with double CEBPA mutations based on next-generation sequencing and its prognostic significance

Abstract: The aim of this study was to profile the spectrum of genetic mutations in acute myeloid leukemia (AML) patients co-occurring with CEBPA double mutation (CEBPAdm). Between January 1, 2012, and June 30, 2017, 553 consecutive patients with de novo AML were screened for CEBPA mutations. Out of these, 81 patients classified as CEBPAdm were analyzed further by a sensitive next-generation sequencing assay for mutations in 112 candidate genes. Within the CEBPA gene itself, we found 164 mutations. The most common mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 22 publications
8
45
0
2
Order By: Relevance
“…Multiple mechanisms for CEBPA inhibition have been identified in leukemic cells, from genetic to epigenetic, from transcriptional to translational and post-translational levels (Table 3, Figure 3). Mutations of CEBPA are also associated with mutations in TET2, the most frequently co-mutated gene (34%), followed by GATA2 (21%), WT1 (13%), DNMT3A (9%) and ASXL1 (9%) [130][131][132][133]. Recently, a direct co-occurrence between CEBPA and granulocyte colony-stimulating factor receptor (CSF3R) mutations has been reported [134,135].…”
Section: Cebpa Mutationsmentioning
confidence: 99%
“…Multiple mechanisms for CEBPA inhibition have been identified in leukemic cells, from genetic to epigenetic, from transcriptional to translational and post-translational levels (Table 3, Figure 3). Mutations of CEBPA are also associated with mutations in TET2, the most frequently co-mutated gene (34%), followed by GATA2 (21%), WT1 (13%), DNMT3A (9%) and ASXL1 (9%) [130][131][132][133]. Recently, a direct co-occurrence between CEBPA and granulocyte colony-stimulating factor receptor (CSF3R) mutations has been reported [134,135].…”
Section: Cebpa Mutationsmentioning
confidence: 99%
“…Mutations in the CEBPA gene occur in 7%-15% of all acute myeloid leukemia (AML) patients [1,2]. However, we found that the frequency of such mutation may be high in Chinese AML patients [3,4]. Although AML with CEBPA double mutations (CEBPA dm ) indicates a favorable outcome, recent data show that more than 50% of patients finally relapsed when consolidated with chemotherapy alone [5].…”
Section: To the Editormentioning
confidence: 99%
“…Just before transplantation, no risk factors except for the mild hepatic dysfunction and age were found, the hematopoietic cell transplantation-comorbidity index (HCT-CI) was 1, and the age-adjusted HCT-CI score was 2 [4,5]. Meanwhile, bone marrow examination revealed active disease with 6.7% myeloblasts.…”
Section: To the Editormentioning
confidence: 99%
“…For example, in AML with CEBPA double mutations, a low-risk group, some patients experience continuous remission, while others relapse after cycles of consolidation chemotherapy or stem cell transplantation. 5 , 6 Studies from different medical centers have attempted to explore new markers for re-stratifying these patients. 7 , 8 Therefore, there is an urgent need to uncover potential markers for AML stratification.…”
Section: Introductionmentioning
confidence: 99%